The Effects of Free Cash Flow on Chinese Listed Companies’ Cross-Border Mergers and Acquisitions Performance - Zhang, Zhen (2014)
There are more and more Chinese listed companies take the cross-border mergers and acquisitions (M&A) in recent year, but the M&A performance are not well in generally. Jensen’s free cash flow (FCF) hypothesis was introduced in 1986. According to the FCF hypothesis, FCF has a negative relationship with M&A performance. This study is to examine the effect of FCF influence on Chinese listed companies’ cross-border M&A performance. In addition, this study also examine the relationship between FCF and corporate ownership structure, and examine the relationship between FCF and type of M&A. The data consist of 39 cross-border M&A deals from 2000 to 2008 and 36 Chinese A-share listed companies from Shanghai Stock Exchange and Shenzhen Stock Exchange. The windows period is 5 years. Data are collected from CSMAR database of Shenzhen GuoTaiAn information Technology (GTA) and Chinese official websites of security. Accounting research methods and Principal component analysis are used to evaluate the M&A performance of every sample deals in this study. Descriptive Analysis and multiple liner regression analysis are used to test the research questions of this study. The results the research present that the FCF has a positive effect on Chinese listed companies cross-border M&A performance. The listed state-owned companies have higher FCF rate than private-owned companies before take cross-border M&A. Companies with higher FCF rate prefer choose horizontal M&A to vertical M&A in cross-border M&A. Private-owned companies’ cross-border M&A performance are better than state-owned companies’. The cross-border vertical M&A performance are better than the cross-border horizontal M&A performance.